Application of the Cooperative Learning Group Resume Learning Model as an Effort to Improve Mathematics Learning Achievement - Iin Nur Komariyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
In this research action aims to improve students' mathematics learning outcomes in addition material using the Cooperative Learning Group Resume learning model. The research was carried out in two cycles, each cycle consisting of 4 stages, namely planning, action, observation, and reflection. The subjects in this study were 23 grade II elementary school students. This research data uses quantitative data. Student activity which includes aspects of student attendance increased from the initial observation of 86% increased to 91 in cycle I and increased to 100% in cycle II. 2) the percentage of students able to do the task from 74% in the initial observation increased to 90% in cycle I and increased to 100% in cycle II. 3) students can ask the teacher from 18% to 61% in cycle I and increase to 78% in cycle II. 4) students can answer teacher's questions from 36% increased to 59% in cycle I and increased to 87% in cycle II. 5) students pay attention to the teacher's explanation, from initial observations 47% increased to 66% in cycle I and increased to 91% in cycle II.